A Uve1p-Mediated Mismatch Repair Pathway in Schizosaccharomyces pombe - Kaur, Balveen (American Society for Microbiology, 1999)
UV damage endonuclease (Uve1p) from Schizosaccharomyces pombe was initially described as a DNA repair enzyme specific for the repair of UV light-induced photoproducts and proposed as the initial step in an alternative excision repair pathway. Here we present biochemical and genetic evidence demonstrating that Uve1p is also a mismatch repair endonuclease which recognizes and cleaves DNA 5′ to the mispaired base in a strand-specific manner. The biochemical properties of the Uve1p-mediated mismatch endonuclease activity are similar to those of the Uve1p-mediated UV photoproduct endonuclease. Mutants lacking Uve1p display a spontaneous mutator phenotype, further confirming the notion that Uve1p plays a role in mismatch repair. These results suggest that Uve1p has a surprisingly broad substrate specificity and may function as a general type of DNA repair protein with the capacity to initiate mismatch repair in certain organisms.